Development of Hole Recognition System Using Rule-Based Technique - Tan, Chee Fai (2001)
The effective integration of CAD/CAM (Computer Aided Design/Computer Aided Manufacturing) is a cornerstone of automation progress. The 'islands of automation' such as CAD, CAPP (Computer Aided Process Planning) and CAM are facing the ineffective communication problem. The CAM cannot be integrated directly into CAD due to the lower level geometrical data in CAD and the higher level manufacturing data in CAM. It is important that each 'island of automation' be linked together in order to achieve the goal of integrated CAD/CAM systems. For the past decades, feature-based representation has become a basic part of research in the CAD/CAM integration. The work on feature-based modelling has developed two main approaches, namely, design by features and feature recognition. The feature recognition approach is developed to extract the manufacturing information that is recognized from the CAD database into the CAM database. The features can be used to subtract higher level manufacturing data from lower level or geometrical computer aided data. The Hole Recognition System is developed to solve the communication problem between CAD and CAM. Kappa-PC expert system is used in developing the rule of holes. In this work, the Hole Recognition System is retrieves the geometrical data from the UniGraphics (UG) CAD/CAM system indirectly. The Hole Recognition System is designed to generalise and recognise the feature from neutral format file such as Data Exchange File (DXF), Initial Graphics Exchange Specification (IGES) and Standard for the Exchange of Product Model Data (STEP). The neutral format file can be created hy CAD/CAM system such as UG, CATIA, ProEngineer, etc. For this work, the neutral data transfer standards, namely STEP is used. The STEP file is post processed by UG CAD/CAM system after the solid model has been created. A filtering program is developed to extract the geometrical data feature recognition process. The filtering program has been developed because the Kappa-PC expert system cannot read the STEP file directly. The output from the filtering program is fed to the Hole Recognition System. The rule-based technique is applied to recognise holes. There are two features, namely, blind hole and through hole to be considered. The work presented in this thesis and the Hole Recognition System developed is able to overcome the communication problem in CAD/CAM. The output from the Hole Recognition System is useful for multiple downstream manufacturing activities such as machine tool selection and cutting tool selection.